Zum Problem kommunikativer Didaktisierungsmöglichkeiten literarischer Texte im Fremdsprachenunterricht - Karolak, Czesław (Studia Germanica Posnaniensia, 2018)
On the basis of the practical attempt at didactization it was found that work with short narrative prose forms, starting from specific elements of communicative process, may stimulate both the simpler activities and the more complex communicative operations and linguistic reactions going in their structure and content beyond the text. Attention was drawn to the role of authenticity of communicative situations initiated by the text - especially with reference to identification of the intentional aspect of the text.